Investimento direto externo e comércio exterior da China nos anos 1990 e 2000 - Cunha, Samantha Ferreira e (2008)
Considering the up ahead tendency of trade and foreign direct investment (FDI) flows in Chinese economy, the present study investigated the relationship between FDI and the changes verified in China s export structure towards high-tech sectors. First, it was examined China s trade pattern of specialization, trough the use of international trade indicators as market-share, revealed comparative advantage (VCR) and contribution to trade balance (CTB) and the geographic pattern of China s foreign trade, considering its main trade partners. Second, it was estimated a model of the determinants of Chinese exports performance, contributing to earlier studies, when considering the different impacts of FDI on export structure classified according to its technological intensity, through time series analyses and VAR model estimation with variance decomposition analysis. The main results confirm the hypothesis that changes in China s trade pattern of specialization converged to international trade evolution, which means that China rose its share in dynamic sectors, that is, sectors that presents an growing foreign demand. This stimulated China s integration with the global trading system and increased the importance of intra-industry trade flows. The econometric estimation suggested that FDI had different impacts among export sectors, which means that, FDI is more efficient in promoting exports from those sectors more technologicalintensive. Besides that, other independent variables utilized in estimation seems to have a better importance than FDI, mainly investment rate, which is consonant with China s economic performance that presents an average growth rate of 10% per year for at least two decades.